Characterizing the bacterial communities associated with Mediterranean sponges: a metataxonomic analysis - Esposito, Roberta; Federico, Serena; Sonnessa, Michele; Reddel, Sofia; Bertolino, Marco; Ruocco, Nadia; Zagami, Giacomo; Giovine, Marco; Pozzolini, Marina; Guida, Marco; Zupo, Valerio; Costantini, Maria (Frontiers in Microbiology, 2024)
The oceans cover over 70% of our planet, hosting a biodiversity of tremendous wealth. Sponges are one of the major ecosystem engineers on the seafloor, providing a habitat for a wide variety of species to be considered a good source of bioactive compounds. In this study, a metataxonomic approach was employed to describe the bacterial communities of the sponges collected from Faro Lake (Sicily) and Porto Paone (Gulf of Naples). Morphological analysis and amplification of the conserved molecular markers, including 18S and 28S (RNA ribosomal genes), CO1 (mitochondrial cytochrome oxidase subunit 1), and ITS (internal transcribed spacer), allowed the identification of four sponges. Metataxonomic analysis of sponges revealed a large number of amplicon sequence variants (ASVs) belonging to the phyla Proteobacteria, Cloroflexi, Dadabacteria, and Poribacteria. In particular, Myxilla (Myxilla) rosacea and Clathria (Clathria) toxivaria displayed several classes such as Alphaproteobacteria, Dehalococcoidia, Gammaproteobacteria, Cyanobacteria, and Bacteroidia. On the other hand, the sponges Ircinia oros and Cacospongia mollior hosted bacteria belonging to the classes Dadabacteriia, Anaerolineae, Acidimicrobiia, Nitrospiria, and Poribacteria. Moreover, for the first time, the presence of Rhizobiaceae bacteria was revealed in the sponge M. (Myxilla) rosacea, which was mainly associated with soil and plants and involved in biological nitrogen fixation.